An investigation into the factors that influence the success of small business in Port Elizabeth - Wilmot, Chloé Margot (Rhodes University, Faculty of Commerce, Department of Management, 2013)
South Africa has one of the highest unemployment rates in the world, currently 23.90%. One way for the government and policy-makers of South Africa to address this dire statistic is through the fostering and promotion of entrepreneurship and small business creation. The benefits of entrepreneurship are numerous and can include: increasing a country's productivity, enhancing the welfare and well-being of its citizens, reducing emigration rates, improving economic development and perhaps, most importantly, increasing employment rates. Worldwide, small businesses within the private sector have become indispensable to sustainable job creation and therefore it is of the utmost importance that small businesses in any economy develop, grow and succeed. Despite the fact that research pertaining to small businesses has increased over the years, little empirical evidence has been established. In particular, research into what makes small businesses successful has been limited. Entrepreneurial activity in South Africa remains less than ideal and therefore it is appropriate that research into the success factors of small businesses in South Africa be investigated. Furthermore, the survival of South African small businesses beyond four to five years of being in operation is estimated at only 20.00%. It is evident that a lack of knowledge exists and with respect to this research the factors found to be the most common determinants of success for small businesses in Port Elizabeth were determined and investigated. Convenience- and snowball sampling techniques were used to identify potential participants. In total 43 usable questionnaires were returned. Methodological triangulation was used to analyse the data, according to descriptive- and inferential statistics, as well as content analysis. This being so, the research was conducted within two paradigms, primarily, the positivist research paradigm and also the phenomenological research paradigm. The key findings of this study indicate personal factors to be the most important success factor group, while the environmental success factor group is considered the least important. The most important factors attributable to the success of participants' small businesses include: maintaining good customer services skills and relationships; having a strong commitment to product/service quality; and having honest employees with sound professional ii knowledge and a positive morale. The least important success factors include: trade exhibitions and business fairs; small business legislation; and industry structure and competition. Finally, the hypothesis tests indicate that significant differences only exist between: the relationship statuses and business factors and the business sectors and environmental factors. The results of this research have significant practical implications for the various stakeholders of entrepreneurship. It is hoped that the results will add to the existing body of knowledge and in turn aid South Africa in becoming aware of the factors essential for small business success. In doing so, South Africa at large will be able to take full advantage of entrepreneurship and small business creation, which continue to remain well within its reach
Keywords: Small business -- South Africa -- Port Elizabeth; Job creation -- South Africa; Entrepreneurship -- South Africa; Success in business -- South Africa